Electrical cardiometry and lung ultrasound in detection of volume overload in pediatric patients on hemodialysis - Elghoul, Sara Mabrouk; Hantash, Hala Ibrahim; Bedair, Hebatallah A.; Moharam, Saad Ahmed; Elsharkawy, Mohammed Said; Elfeky, Yomna Gaber Hassan (The Turkish Journal of Pediatrics, 2026)
Background. Assessment of volume overload and determination of dry weight are essential for children on hemodialysis (HD). This study aimed to compare the effectiveness of lung ultrasound (LUS)-derived B-lines and electrical cardiometry (EC)-derived thoracic fluid content (TFC) scores in detecting volume overload in pediatric patients undergoing maintenance HD.Methods. This cross-sectional study was conducted on 50 patients aged 5 to 18 years, both sexes, with kidney failure on maintenance HD three times weekly. Dry weight was determined for each patient by a pediatric nephrologist based on a clinical assessment of hydration status (absence of edema, pulmonary rales, hypertension, intradialytic hypotension or cramps) and supported by bioimpedance spectroscopy values to estimate overhydration. Patients who did not reach dry weight at the end of the session were defined as the non-dry weight group (N=21) and those who did were defined as the dry weight (N=29) groups. Correlations of B-lines and TFC with clinical parameters and the diagnostic performance of these methods in predicting hypervolemia (ROC analysis) were analyzed.Results. Before dialysis, TFC and B-line scores did not differ significantly between the dry-weight and non-dry-weight groups (P>0.05), but were significantly lower after the HD session in the dry weight group than in the non-dry weight group (P < 0.001). TFC and B-line scores could significantly predict hypervolemia (areas under the curve [AUC]: 0.750 and 0.801, respectively). In the same order the cut off values were >31 kOhm⁻¹ and >17, sensitivities were 76.19% and 80.95%, and specificities were 55.71% and 75.86%, respectively. TFC was comparable to the B-line score in the prediction of hypervolemia (P=0.585, difference between AUCs=0.050; 95% confidence interval: -0.132 to 0.234).Conclusions. Both LUS and EC are valuable bedside methods for assessing volume overload in pediatric HD patients. However, EC is not as dependent on operator skills and may be a valuable tool in clinical practice, especially in settings where LUS might be challenging to perform.
Keywords: lung ultrasound; electrical cardiometry; extravascular lung water; hemodialysis; pediatric